Prehabilitation for Cancer Surgery - Chakraborty, Arunangshu; Balakrishnan, Ashokka; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book explores the concept of prehabilitation to great depths using all possible modes of prehabilitation across surgical specialities. Prehabilitation is a unique concept that is becoming popular day-by-day. It began from the enhanced recovery after surgery (ERAS) program and has found importance in almost all of the surgeries now. The book possibly being the first on prehabilitation globally introduces the concept, describes the methods of functional assessment of the patients scheduled for extensive cancer surgery, and ways of pre-optimisation. It covers the methods of prehabilitation system-wise and then provides pehabilitation tools specific for individual onco-surgical subspecialties. The book will be an invaluable resource for practitioners of onco-anesthesia and onco-surgery in optimizing their patients before surgery for best results. It will also be useful for the allied disciplines such as nutritionists, physiotherapists, psychiatrists and oncology nurses.
Section I: Introduction to Prehabilitation -- Concept of prehabilitation -- Functional assessment: MET, ECOG -- Section II: Systemic Prehabilitation -- Cardiovascular prehabilitation -- Respiratory prehabilitation -- Endocrine prehabilitation -- Hematological prehabilitation -- Nutritional prehabilitation -- Role of Physiotherapy in prehabilitation -- Psychological and social prehabilitation -- Section III: Prehabilitation for Cancer Surgery- Speciality wise -- Prehabilitation for Liver, hepato-pancreato-biliary surgery -- Prehabilitation for Colorectal surgery, ERAS elements -- Prehabilitation for thoracic surgery -- Prehabilitation for uro-gynae-oncological surgery -- Prehabilitation for head and neck onco-surgery -- Prehabilitation for Skeletal/muscular cancer surgery.
Keywords: Anesthesiology; Oncology; Surgery; Physical therapy; Nursing; Anesthesiology; Oncology; Surgery; Physiotherapy; Nursing; Neoplasms -- surgery; Neoplasms -- rehabilitation